Chemical profiling of damaged local yellow corn grains - Yu, Amy April Amor M. ([Miag-ao, Iloilo] University of the Philippines Visayas, 2016)
A rigid evaluation of the chemical and physical profile of damaged yellow corn was conducted in this study. Proximate analysis, aflatoxin analysis, bushel weight determination, and starch analysis were done on good, spoiled, moldy, and insect-damaged grains. Metabolizable energy was then computed. From the statistically analyzed data, moldy grains showed significant difference from the control for almost all analysis except for starch. Aflatoxin analysis showed significantly high concentrations. This can pose a challenge if moldy grains are incorporated into feedsbecause of aflatoxin effects on both animals and humans. The analysis of spoiled grains and insect-damaged grains on crude protein, crude fat, crude fiber, ash, bushel weight, and aflatoxin showed significant difference with the control. The metabolizable energy, however, was not significant with the control but highly significant with other types of damage. The low bushel weight of insect-damaged corn can be attributed to the loss in weight when insects bored the corn. Aflatoxin contamination is spread by the insects during infestation and this is reflected in higher aflatoxin concentrations. Generally, results show that local yellow corn damage brought by spoilage, molds, and insects have lower nutritive value. This should be given attention by Animal Nutritionists or Formulators as well as the farmers. Further chemical analyses are recommended for proper assignment of nutrient value taking into account loss in nutrients due to the damage of the grains, farmers can be compensated with the appropriate cost of money. An increased awareness in the proper handling and storage of their grains can also help them in improving grain quality.
Special Problem (M. Chemistry) -- Miagao, Iloilo : University of the Philippines Visayas, December 2016.